Can climate change mitigation policy benefit the Israeli economy? A computable general equilibrium analysis - Ruslana Palatnik; Mordechai Shechter (Fondazione Eni Enrico Mattei (FEEM), 2008)
The growing attention to global warming due to greenhouse gas (GHG) emissions in the process of fossil fuel-based energy production is expressed in the Kyoto Protocol, which prescribes, on average, a 7 percent reduction in GHG emissions for developed countries. Although Israel was not included in the list of the obligated countries ('Annex A'), it should consider the economic implications of participating in the emission reduction effort, as such a commitment becomes highly feasible following the Bali roadmap which oblige a successor to the Kyoto Protocol to launch negotiations including all parties to the UNFCCC on a future framework, stressing the role of cooperative action and of common though differentiated responsibility. This study aimed to quantify the economy-wide consequences for Israel of meeting the targets of the Kyoto Protocol, employing a Computable General Equilibrium (CGE) model of the Israeli economy. Initially, to this end, we constructed a social accounting matrix (SAM) to serve as a benchmark by combining physical energy and emission data and economic data from various sources. The efficacy of decentralized economic incentives for CO2 emission reduction, such as carbon taxes on emissions and auctioned emission permits, was assessed in terms of their impact on economic welfare. In addition, we tested for the ensuing so-called double dividend. Two distinct cases were analyzed. In the first one, we tested a revenue-neutral environmental policy which proportionally cut pre-existing taxes. Labour supply was assumed to be exogenously fixed. The results showed that, although significant CO2 emission reduction can be achieved, followed by modest economic cost, no double dividend could be discerned. Next, in order to check for the employment double dividend (lower CO2 emissions and lower unemployment), we introduced labor market imperfections, with the aim of cutting income tax. The results of this case indicate that an employment double dividend is possible under a rather standard set of assumptions. Moreover, for higher substitutability between the energy composite input and the labor-capital one, an even 'strong' form of double dividend can be obtained. We performed several sensitivity analyses with respect to the modeled production function, which re-confirmed the finding that higher substitution possibilities lead to lower welfare costs 3 associated with a given emission reduction target. We qualify this general result by also showing that the opposite holds when the emission tax rate is held constant, rather than reduced. It may be concluded on the basis of this analysis that a double dividend may be an achievable goal under a GHG emission reduction policy in the case of economies such as Israel. The CGE approach applied in this research is adopted for the first time to the Israeli economy and should contribute to better informed debate on environmental policy in Israel.
Keywords: D58; H23; Q43; Q48; Q52; 330; Treibhausgas; Klimaveränderung; Klimaschutz; Umweltpolitik; Wirkungsanalyse; Doppelte Dividende; Allgemeines Gleichgewicht; Israel